On the summability of the spectral expansions of distributions - Rakhimov, Abdumalik (2015)
This paper is about first results on the summability of the spectral expansions of distributions from the Sobolev spaces with negative smoothness. These results were obtained by Prof. Shavkat Alimov in 1993 and have led to the development of new interesting research directions of the spectral theory of differential operators.